Multi-frequency ultrasound imaging: phantom study - Abdul Malek, Siti Nur Masturah; Sayed, Inayatullah Shah (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2018)
Introduction: In ultrasound imaging there is compromise between the penetration of signal at certain depths into the object and image resolution as the ultrasound probe only can transmit single frequency signals in one transmission. Using curvilinear ultrasound probe with 2 to 5 MHz frequency bandwidth, this study investigated the use of multi-frequency imaging to enhance the quality of phantom images. Methods: Siemens Acuson X150 with curvilinear ultrasound transducer was used to scan the organs of interest (kidney, gallbladder and pancreas) of the ultrasound abdominal phantom. Different images at the different selected frequencies (2.5, 3.6 and 5.0 MHz) were created by fixing the position and the orientation of the transducer in each of the scanning process. Different-frequency images were generated and combined to produce composite (multi-frequency) image. Results: In this study, the quality of the composite images was evaluated based on signal-to noise ratio (SNR) and the obtained results were compared with the single frequency images. Besides, the comparison was also made in terms of overall image quality (noise and sharpness of organ outline) through perceived image quality analysis. Based on calculated SNR, the composite image of the kidney, gallbladder and pancreas recorded higher SNR value as compared to the single frequency images. However, through perceived image quality, most of the observers viewed that the quality of the composite image of the kidney, gallbladder and pancreas is poor as compared to the single frequency image. Conclusions: Image quality of ultrasound imaging is improved by combining multiple ultrasound frequency images into a single composite image. This is achieved as high SNR is obtained in the composite image. However, through perceived image quality, the overall image quality of the composite image was poor.